2019
DOI: 10.1039/c8dt04698k
|View full text |Cite
|
Sign up to set email alerts
|

Evans–Showell-type polyoxometalate-based metal–organic complexes with novel 3D structures constructed from flexible bis-pyrazine–bis-amide ligands and copper metals: syntheses, structures, and fluorescence and catalytic properties

Abstract: Two 3D Evans–Showell-type POM-based copper–bis-pyrazine–bis-amide complexes show good heterogeneous catalytic activity for the oxidation of benzyl alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…In metalloenzymes, carboxylate side chains of the peptide are very frequent ligands and were preferably coordinated by hard metal ions, as expected. In contrast to this, carboxamide side chains were less preferred as ligands in metalloenzymes [34][35][36], in agreement with the observation that the carboxamide function coordinates only effectively in chelate ligands as 2-pyridine or 2-pyrazine carboxamides [1][2][3]5,6,[15][16][17][18][19][20][22][23][24][25][26]32,[37][38][39][40][41].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…In metalloenzymes, carboxylate side chains of the peptide are very frequent ligands and were preferably coordinated by hard metal ions, as expected. In contrast to this, carboxamide side chains were less preferred as ligands in metalloenzymes [34][35][36], in agreement with the observation that the carboxamide function coordinates only effectively in chelate ligands as 2-pyridine or 2-pyrazine carboxamides [1][2][3]5,6,[15][16][17][18][19][20][22][23][24][25][26]32,[37][38][39][40][41].…”
Section: Introductionsupporting
confidence: 64%
“…Non-chelated Oamide binding to Cu II was found in the axial (weak) positions only in one compound (2) and no NH2amide coordination, in line with the observation that amide functions in amino acids do not represent an important class of ligands in metalloproteins [34][35][36] and the poor non-biologic coordination chemistry of amides and Cu [33,35,37]. Indeed, searching the CCDC database, gave only the Cu II complex [Cu(L)2(OH)2] containing two chelating pyrazine-2,3dicarboxamide ligands with Cu-NH2amide bonds [49].…”
Section: X-band Epr Spectroscopy and Magnetic Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…The oxidation of alcohols to the corresponding carbonyl compounds is a critical transformation in organic synthesis. Many catalytic systems, homogeneous or heterogeneous, have been developed for the oxidation of alcohols, forming corresponding aldehydes, carboxylic acids, or esters depending on the level of oxidation and esterification, with poor or satisfactory yields depending on the catalytic system. ,, Despite the progresses made toward this end, available catalysts are still limited with versatile disadvantages, such as the need of harsh reaction conditions, the involvement of noble or toxic metals, the use of costly cocatalysts, and poor recyclability. To the best of our knowledge, there are no attempts utilizing visible light to mediate the oxidation reaction. The development of a photocatalytic system utilizing a highly efficient heterogeneous catalyst with good recyclability is of great importance in terms of green chemistry. …”
Section: Resultsmentioning
confidence: 99%
“…For instance, two Evans-type POMbased complexes constructed from two different bis-pyridinebis-amide ligands, synthesized by Li et al showed excellent catalytic oxidation performance. 29 By introducing the bis-pyrimidine-bis-amide ligand N,N′-bis-(4-pyrimidinecarboxamido)-1,2-ethane (4-H 2 dpye), two Keggin-type POM-based MOCs were successfully synthesized by our group with excellent electrochemical sensing behavior, which could be used as supercapacitor materials. 30 In view of this, two new bis-pyridine-bis-amide ligands, namely 4,4′-bis(3-pyridinecarboxamide)phenylmethane (L 1 ) and, 4,4′-bis(3-pyridinecarboxamide)phenylketone (L 2 ), were designed and synthesized (Scheme 1), and further used to assemble with Anderson-type POMs and Co II ions.…”
Section: Introductionmentioning
confidence: 99%